A descentralização normativa do ICMS como causa impeditiva da eficiência fiscal - Silva, Fatima Rega Cassaro da (2016)
This study aims to analyze the regulatory framework of the tax on circulation of goods - ICMS, whose tax jurisdiction has been assigned by the Constitution to the States and Federal District, and It has been delegated to Complementary Law regulating the general rules of this tax. This instrument was chosen by the constituent legislator as a way to enable a unified guideline to be followed by States and Federal District to institute this tax. However, this instrument has proved insufficient to prevent conflicts between the States and the Federal District, as it does not determine parameters to be followed in situations such as: (i) granting tax benefits; (ii) setting rules for accessory obligations institution and (iii) definition of rules for calculating the tax in the scheme of tax substitution. As a result, it has this legal instrument not actually unifies the institution of this tax. So what is intended with this study is to reflect on the ICMS regulatory framework in order to verify if the biggest problems regarding this structure arise from the normative decentralization due to the autonomy of each of the 27 different States.